Acutely Obstructed Airway Resulting from Complications of a Laryngopyocoele. (18th May 2017) - Mole, Rosalind; Hayes, Stephen; Dennis, Simon
Abstract : Laryngocoeles are rare cystic dilatations of the laryngeal ventricle. Obstruction of its outlet can cause entrapment of mucus and superimposed infection causes a laryngopyocoele. Such presentations, although rare, have potential to cause airway obstruction. A 67-year-old lady presented with a one-week history of hoarseness and shortness of breath. On examination, she was stridulous and had fullness of the left side of the neck. Nasendoscopy revealed large bilateral vocal cord polyps and near-complete glottis obstruction. She was taken to emergency theatre for restoration of a viable airway. Upon excision of the polyps, pus was visualised originating from the laryngeal ventricle. Literature proposes that laryngocoeles develop secondary to a one-way valve caused by an obstructing lesion distorting the saccule neck. We propose that the laryngocoele developed secondary to large obstructing polyps. Urgent excision of the polyps allowed decompression of the laryngopyocoele and reestablishment of a patent airway.